ANALISIS USABILITY SISTEM INFORMASI LAYANAN MANDIRI DI PERPUSTAKAAN UNIVERSITAS BRAWIJAYA - Kurniasih Yuni Pratiwi; Suprihatin Suprihatin (Central Library of Universitas Sebelas Maret, 2019)
Information Technology makes things easier, the existence of a library in an institution of higher education is very important needed by all academicians, to realize a digital library and library services that are ideal for users is not an easy job. The Brawijaya University library has implemented a book lending independent service and book extensions for its visitors, so that users can feel comfortable and satisfied when utilizing the services available in the library. The independent service system in UB's Library as a form of transformation of the university library in improving the ideal service for visitors.The purpose of this study was to determine the usability analysis of independent service information systems in the Brawijaya University Library. This research is a quantitative descriptive study, using the theory of usability to determine the evaluation of self-service systems, the method used is a survey with a sample of 100 students. Hypothesis testing and data processing in this study using Partial LeastSquares(PLS).The results of this study indicate that there are 4 hypotheses that have been empirically proven to affect the usability of independent services in the Brawijaya University Library, namely the variables of Learnability, Efficiency, Memorability, Satisfaction (user satisfaction). 1 hypothesis is empirically proven to have no effect, namely the Few error variable (some errors), so that the UB library should innovate to improve services to users by submitting a mobile android based book loan application design. The intended application is intended so that the library user can borrow books independently only with the smartphone the user has.